ABUNDANCES OF HEAVY ELEMENTS IN SIRIUS (Z>72) - Yushchenko, A. V. (Одеські астрономічні публікації, 2017)
The abundances of eight heavy elements: Hf, Ta, W, Re, Os, lr, Hg and Pb are found in the atmosphere of Sirius A. The Copernicus UV spectral atlas is used. The investigated elements show the overabundances with respect to the Solar system values in the range 07-27 dex.